Factors Influencing Work Readiness and Student Satisfaction in Technical Education: A Systematic Review of Industry Collaboration, Certification, and Academic Engagement - Rahmat Desman Koto; Wagino Wagino; Hasan Maksum; Eko Indrawan; M Giatman (STKIP Singkawang, 2025)
This study systematically examines the factors that affect students' job readiness and satisfaction in engineering education through a comprehensive analysis of industry support, certification programs, and academic engagement. The Industrial Revolution 4.0 era has created a significant skills gap between graduate competencies and industry needs, demanding innovative approaches in the preparation of work-ready graduates. Through the Systematic Literature Review (SLR) which follows PRISMA's guidelines for articles obtained from the ScienceDirect database during the period 2017-2024, this study integrates evidence from multiple theoretical frameworks including experiential learning theory, social cognitive theory, and human capital theory. Of the 800 articles identified through ScienceDirect's database search, after going through a rigorous PRISMA selection process with quality assessment using the Mixed Methods Appraisal Tool (MMAT), 185 high-quality articles were successfully selected and analyzed in depth. Key findings show a significant positive relationship between industry-university collaboration, the implementation of professional certification programs, and active academic involvement to improving job readiness and student satisfaction. The analysis revealed that the implementation of industrial internship programs (94% effectiveness, satisfaction score 4.6/5.0), industry-specific competency certification (satisfaction rating 4.4/5.0), and extracurricular activities such as capstone projects and engineering competitions can significantly increase employability. Nonetheless, systemic challenges such as curriculum gaps with industry needs (identified in 68.1% of studies), limited faculty experience in industry (53% of studies), and infrastructure limitations (47% of studies) remain structural barriers that require comprehensive solutions. This research provides an evidence-based framework for transforming technical education toward more industry-relevant, student-centered approaches and provides actionable recommendations for educational practitioners, policymakers, and industry partners.